Cancer‐Associated Fibroblasts: Interfacial Curvature in Confined Coculture Directs Stromal Cell Activity with Spatial Corralling of Pancreatic Cancer Cells (Adv. Biology 6/2021). Issue 6 (16th June 2021) - Nemec, Stephanie; Lam, Joey; Zhong, Jingxiao; Heu, Celine; Timpson, Paul; Li, Qing; Youkhana, Janet; Sharbeen, George; Phillips, Phoebe A.; Kilian, Kristopher A.
Abstract : In article number 2000525, Kristopher A. Kilian and co‐workers show immunofluorescent staining of collagen I (orange), α‐smooth muscle actin (red), pancreatic cancer (green), and nuclei (blue) co‐cultures of pancreatic cancer‐associated fibroblasts and cancer on flower, circle, and star micropatterned polyacrylamide gels.